POTENSI PENGEMBANGAN PEMBANGKIT LISTRIK PANASBUMI SUHU RENDAH DI KABUPATEN PEGUNUNGAN ARFAK PROVINSI PAPUA BARAT: POWER PLANT DEVELOPMENT POTENTIAL GEOTHERMAL LOW TEMPERATURE IN MOUNTAIN DISTRICT ARFAK WEST PAPUA PROVINCE - Agustinus Denny Unggul Raharjo (JISTECH: Journal of Information Science and Technology, 2015)
Arfak Highlands Regency is a new autonomous region in West Papua Province with abundant naturalresources. As new autonomous region Arfak Highlands Regency will experienced significant population growth.Population growth along with development and modernization will give burden to electricity demand.Alternatively, electricity could be provides with geothermal resources in Minyambouw District. Based on surveyconducted by the Government trough The Geology Resources Centre in 2009, the reservoir temperature of thegeothermal sources is 86oC with non volcanic geothermal system. Thus, the geothermal resources in ArfakHighlands Regency could be developed into binary cycle electric generator.